2015
DOI: 10.1093/jxb/erv236
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence of the plant elicitor peptides (Peps) and their receptors: interfamily incompatibility of perception but compatibility of downstream signalling

Abstract: HighlightPlant elicitor peptides (Peps) co-evolved with their receptors, resulting in interfamily incompatibility of Pep recognition. In contrast, operation of defence pathways by Pep receptors is conserved within the flowering plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 38 publications
5
96
1
10
Order By: Relevance
“…As shown in Table 2 , the alkalinization effect of AtPEP from Arabidopsis is significantly stronger in Arabidopsis suspension cells, while systemin from potato stimulated alkalinization only in potato suspension cells. These results are consistent with previous reports showing species specificity in the peptidic DAMPs (Lori et al, 2015). …”
Section: Resultssupporting
confidence: 94%
“…As shown in Table 2 , the alkalinization effect of AtPEP from Arabidopsis is significantly stronger in Arabidopsis suspension cells, while systemin from potato stimulated alkalinization only in potato suspension cells. These results are consistent with previous reports showing species specificity in the peptidic DAMPs (Lori et al, 2015). …”
Section: Resultssupporting
confidence: 94%
“…PmPROPEP1 corresponds to PmPROPEP5, described in Lori et al . (). (c) Depiction of the consensus sequences of aligned Rosaceae‐specific Pep sequences using the WebLogo tool (Crooks et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Most plant species contain one or two PEPRs, and conservation of their Pep‐recognition LRR domain is lower than that of the catalytic kinase domain (Flury et al ., ; Huffaker et al ., ; Lori et al ., ; Yamaguchi et al ., ). Peps from a given plant species can only be perceived by plants from the same family (Huffaker et al ., ; Lori et al ., ), even though downstream pathways leading to PTI seem to be highly conserved among species (Lori et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, analysis of the crystal structure of the At-PEP1-PEPR1 complex revealed that At-PEP1 adopts a fully extended conformation and binds to the inner surface of the superhelical extracellular LRR domain of PEPR1 (Tang et al, 2015). The LRR domains of PEPRs coevolved with the PEPs, leading to distinct PEP motifs in each plant family and interfamily incompatibility of recognition, in contrast to the highly conserved downstream signaling (Lori et al, 2015). In general, the PEP immune signaling pathway is associated with an early cytosolic Ca 2+ influx that activates protein kinases, reactive oxygen species, and nitrogen oxide .…”
Section: Non-cysteine-rich Peptides Without Specific Posttranslationamentioning
confidence: 99%